Sustainable Water Treatment : Engineering Solutions for a Variable Climate - Scholz, Miklas (Elsevier, 2019)
Sustainable Water Treatment: Engineering Solutions for a Variable Climate covers sustainable water and environmental engineering aspects relevant for the drainage and treatment of storm water and wastewater. The book explains the fundamental science and engineering principles for the student and professional market. Standard and novel design recommendations for sustainable technologies, such as constructed wetlands, sustainable drainage systems and sustainable flood retention basins are provided to account for the interests of professional engineers and environmental scientists. The book presents the latest research findings in wastewater treatment and runoff control that are ideal for academics and senior consultants. The book offers a challenging, diverse, holistic, multidisciplinary, experimental and modelling-orientated case study, covering topics such as natural wetlands, constructed treatment wetlands for pollution control, sustainable drainage systems managing diffuse pollution, specific applications, such as wetlands treating dye wastewater and ecological sanitation systems recycling treated waters for the irrigation of crops.